Neurodevelopmental outcomes in HIV-exposed-uninfected children versus those not exposed to HIV - Stephen J. Kerr (2018)
Human immunodeficiency virus (HIV)-negative children born to HIV-infected mothers may exhibit differences in neurodevelopment (ND) compared to age-and gender-matched controls whose lives have not been affected by HIV. This could occur due to exposure to HIV and antiretroviral agents in utero and perinatally, or differences in the environment in which they grow up. This study assessed neurodevelopmental outcomes in HIV-exposed uninfected (HEU) and HIV-unexposed uninfected (HUU) children enrolled as controls in a multicenter ND study from Thailand and Cambodia. One hundred sixty HEU and 167 HUU children completed a neurodevelopmental assessment using the Beery Visual Motor Integration (VMI) test, Color Trails, Perdue Pegboard, and Child Behavior Checklist (CBCL). Thai children (n = 202) also completed the Wechsler Intelligence Scale (IQ) and Stanford-Binet II memory tests. In analyses adjusted for caregiver education, parent as caregiver, household income, age, and ethnicity, statistically significant lower scores were seen on verbal IQ (VIQ), full-scale IQ (FSIQ), and Binet Bead Memory among HEU compared to HUU. The mean (95% CI) differences were-6.13 (-10.3 to-1.96), p = 0.004;-4.57 (-8.80 to-0.35), p = 0.03; and-3.72 (-6.57 to-0.88), p = 0.01 for VIQ, FSIQ, and Binet Bead Memory, respectively. We observed no significant differences in performance IQ, other Binet memory domains, Color Trail, Perdue Pegboard, Beery VMI, or CBCL test scores. We conclude that HEU children evidence reductions in some neurodevelopmental outcomes compared to HUU; however, these differences are small and it remains unclear to what extent they have immediate and long-term clinical significance. © 2014 Taylor and Francis.